Cavity Expansion Methods in Geomechanics - Yu, Hai-Sui (Springer Netherlands, 2000)
Cavity expansion theory is a simple theory that has found many applications in geotechnical engineering. In particular, it has been used widely to analyse problems relating to deep foundations, in-situ testing, underground excavation and tunnelling, and wellbore instability. Although much research has been carried out in this field, all the major findings are reported in the form of reports and articles published in technical journals and conference proceedings. To facilitate applications and further development of cavity expansion theory, there is a need for the geotechnical community to have a single volume presentation of cavity expansion theory and its applications in solid and rock mechanics. This book is the first attempt to summarize and present, in one volume, the major developments achieved to date in the field of cavity expansion theory and its applications in geomechanics. Audience: Although it is intended primarily as a reference book for civil, mining, and petroleum engineers who are interested in cavity expansion methods, the solutions presented in the book will also be of interest to students and researchers in the fields of applied mechanics and mechanical engineering
Keywords: Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Mechanics; Appl.Mathematics/Computational Methods of Engineering; Earth sciences; Geotechnical engineering; Applied mathematics; Engineering mathematics; Wachstum; Geotechnik; Kaverne